Short-term effects of exposure to PM2.5, PM10, NO2, CO, SO2, O3 on lung function test indices among students of Tehran city, Iran - Siavash Kooranifar (Tehran University of Medical Sciences, 2021)
Introduction: The adverse health effects of air pollution have been observed in many epidemiological studies. The aim of this research was to study the effects of air pollution on pulmonary functions in schoolchildren in Tehran city.